All-Polymer Solar Cells Based on Wide-Band Gap Conjugated Polymers - Meng, Jiaoyang (Transactions on Computer Science and Intelligent Systems Research, 2024)
Recently, there has been an increased utilization of wide bandgap polymer electron donors in non-fullerene organic polymer solar cells. Consequently, scientists and engineers worldwide have shown substantial interest and research focus on all-polymer solar cells utilizing wide bandgap conjugated polymers. These advanced materials provide distinct benefits in terms of adjustable electronic properties, superior effectiveness, and possibility for cost-effective manufacturing, making them a central focus for the advancement of future solar energy technologies. This article will begin by giving a detailed summary of the progression of all-polymer solar cell development in recent decades. We will track the major achievements and advancements that have influenced the field of organic photovoltaics, from its earliest discovery to the most recent progress in polymer chemistry and device engineering. This historical viewpoint will focus on the continuous initiatives and advancements that have propelled the enhancements in performance and expanded the range of applications for polymer solar cells. Afterwards, the article will outline the fundamental layout and functioning principles of polymer solar cells. We will investigate the basic elements such as the active layer, charge transport layers, and electrodes, and demonstrate how these components work together to convert sunlight into electrical energy. In conclusion, the paper will explore the studies on donor materials of conjugated polymers with wide bandgaps. These materials are now seen as crucial elements needed to improve power conversion efficiencies and enhance stability in polymer solar cells.